IoT Monitoring System for Vending Machine - Nisaa Yasmin bt Nor Izuddin; Huda bin A Majid (Progress in Engineering Application and Technology, 2021)
This project is to develop an IoT Monitoring System for VendingMachine which could solve the problem of vending machine owners having tomanually go to the vending machine and check the stocks. A prototype of wirelessremote access for the vending machine was made by using a few components andthe Blynk app on the phone to develop an IoT monitoring system for the status andavailability of product which also provides an end user platform. The prototypeconsists of two parts, the dummy VMC and also a NodeMCU connected to the WiFinetwork. The prototype works when the dummy VMC displays the number ofstocks on the display attached and the Blynk app displaying the same number on thedummy VMC. This project is to help vending machine owners in restocking byreducing the cost of transportation and manpower to restock the items. Bydeveloping this project and implementing IoT, the interest of the audience in theelectronic industry in the vending machine area will be enhanced. This projectreport will fully provide the complete information and progress on how the IoTmonitoring system for vending machine is made.